Psychoeducation Improves Self Esteem in Early Adult Victims of Dating Violence - Djudiyah; Halimatus Sa'ida (Penerbit Jurnal Indonesia, 2026)
This study aims to determine the effect of psychoeducation on increasing self-esteem in young adult women who are victims of dating violence. The study used a quantitative approach with a quasi-experimental one-group pretest-posttest design. The study subjects were 10 young adult women who had experienced or were experiencing dating violence. Data were analyzed using a Paired Sample t-Test. The results showed that there was a difference in self-esteem before and after psychoeducation (t = -0.997) (p = 0.345). The mean post-test (Mean = 6.50) was higher than the mean post-test (Mean = -5.60). Thus, psychoeducation can increase self-esteem. The conclusion of this study is that it has a positive impact on improving self-esteem in young adult female victims of dating violence. Changes in scores indicate that psychoeducation is beneficial as an initial step in recovery, but further interventions with longer duration and intensity are needed for optimal results.